Sexual Function Of Malay Women With Type 2 Diabetes Mellitus: A Preliminary Study - Kamaralzaman, S; Sidi, H; Yau, M; Budin, SB; Sani, A.; Mohamed, J (Asean Federation Psychiatry & Mental Health, 2024)
Indexed by WOS